Joseph Auslander papers - Auslander, Joseph, 1897-1965.
TLS (1943 June 7) and ALS (1943 July 11) from Sinclair Lewis and TLS (1943 June 9) from Booth Tarkington written to Auslander as gift officer, Library of Congress.
Author and editor. Library of Congress Consultant in Poetry and Gift officer, Library of Congress.
Collection material in English.
Collection related to the Library of Congress Archives.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lewis, Sinclair, -- 1885-1951 -- Correspondence; Tarkington, Booth, -- 1869-1946 -- Correspondence; Library of Congress -- Officials and employees; Authors; Editors